Noninvasive Imaging of Endothelial Damage in Patients With Different HbA 1c Levels: A Proof-of-Concept Study - Engel, Leif-Christopher; Landmesser, Ulf; Goehler, Alexander; Gigengack, Kevin; Wurster, Thomas-Heinrich; Manes, Costantina; Girke, Georg; Jaguszewski, Milosz; Skurk, Carsten; Leistner, David M; Lauten, Alexander; Schuster, Andreas; et al. (Diabetes (New York, N.Y.), 2019)
The aim of this study was to compare endothelial permeability, which is considered a hallmark of coronary artery disease, between patients with different HbA levels using an albumin-binding magnetic resonance (MR) probe. This cross-sectional study included 26 patients with clinical indication for X-ray angiography who were classified into three groups according to HbA level (<5.7% [<39 mmol/mol], 5.7-6.4% [39-47 mmol/mol], and ≥6.5% [48 mmol/mol]). Subjects underwent gadofosveset-enhanced coronary magnetic resonance and X-ray angiography including optical coherence within 24 h. Contrast-to-noise ratios (CNRs) were assessed to measure the probe uptake in the coronary wall by coronary segment, excluding those with culprit lesions in X-ray angiography. In the group of patients with HbA levels between 5.7 and 6.4%, 0.30 increased normalized CNR values were measured, compared with patients with HbA levels <5.7% (0.30 [95% CI 0.04, 0.57]). In patients with HbA levels ≥6.5%, we found 0.57 higher normalized CNR values compared with patients with normal HbA levels (0.57 [95% CI 0.28, 0.85]) and 0.26 higher CNR values for patients with HbA level ≥6.5% compared with patients with HbA levels between 5.7 and 6.4% (0.26 [95% CI -0.04, 0.57]). Additionally, late atherosclerotic lesions were more common in patients with high HbA levels (HbA ≥6.5%, = 14 [74%]; HbA 5.7-6.4%, = 6 [60%]; and HbA <5.7%, = 10 [53%]). In conclusion, coronary MRI in combination with an albumin-binding MR probe suggests that both patients with intermediate and patients with high HbA levels are associated with a higher extent of endothelial damage of the coronary arteries compared with patients with HbA levels <5.7%.